Dataset on water stress and soil pH effects in Canavalia brasiliensis - Madera Doria, Yaira Yulieth; Madera Doria, Pascual; Mayorga Cobos, Mildred Julieth; Cardoso Arango, Juan Andres (2026)
Canavalia brasiliensis is a tropical forage legume of high agronomic and ecological value, widely recognized for its ability to enhance the productivity and sustainability of livestock systems in tropical and subtropical regions. This species is characterized by high biomass production, good palatability, and adequate crude protein content, making it a strategic alternative for animal feeding, particularly during periods of forage scarcity. This dataset provides information on the response of Canavalia brasiliensis genotypes to water stress and different soil pH conditions. To generate the data, three genotypes of C. brasiliensis were established under water stress (drought) and two soil pH conditions (acidic and neutral). Each experimental unit (genotype × water stress × soil pH) was replicated six times. The dataset includes measurements taken every two days using MultispeQ and QualitySpec over a five-week period. Final harvest data includes leaf area, number of leaves, number of stems, soil moisture, photographic records of the root system, root biomass, and aboveground biomass. This dataset is useful for evaluating the physiological, morphological, and productive responses of C. brasiliensis genotypes to the interaction between water stress and soil pH, allowing for analysis of genetic variability and phenotypic plasticity under contrasting environmental conditions. Periodic measurements with MultispeQ and QualitySpec, combined with final biomass and root system data, facilitate the identification of early indicators of stress tolerance and support studies on genetic improvement and sustainable management of forage legumes in tropical systems. Methodology:Plant material, experimental design, and study site: In this study, seeds from three Canavalia brasiliensis genotypes were used, obtained from the germplasm collection of the Genetic Resources Program of the Bioversity Alliance and CIAT. The seeds were established in a sandy loam Vertisol characterized by high fertility and a pH of 7.5 (neutral) and in a clay loam Ultisol with a pH of 4.5 (acidic). The experiment followed a completely randomized design with a 2 × 2 × 3 factorial arrangement, conducted in soil cylinders under semi-controlled conditions: • Factor 1: Soil acidity (neutral pH and acidic pH) • Factor 2: Water stress (control and drought) • Factor 3: C. brasiliensis accession (7318, 17009, and 17462) Each seed was grown in a PVC cylinder containing 8,250 kg of soil for acidic pH and 7,750 kg for neutral pH soil. Each combination (genotype × water stress × soil pH) was replicated six times. The trial was conducted in a greenhouse equipped with rails to control sunlight exposure during the day and allow coverage to prevent dew formation. The greenhouse is located on the CIAT campus in Palmira, Valle del Cauca, Colombia.